Corporate Social Responsibility Disclosure, Environmental Performance, and Tax Aggressiveness - Sari, Dahlia; Tjen, Christine (Universitas Prasetiya Mulya, 2016)
This study aims to examine the influence of the corporate taxpayers’ level of CSR disclosure and environmental performance on the level of tax aggressiveness. This study took a sample of non-financial companies listed on the Indonesian Stock Exchange during 2009-2012. This study shows that the corporate taxpayers’ level of CSR disclosure has significant negative effect towards the tax aggressiveness. It means the higher the level of the CSR disclosure, the lower the company’s tax aggressiveness. This study also proves that good environmental performance will strengthen the negative effect of CSR disclosure on tax aggressiveness. The assessment of environmental performance is conducted by the Ministry of Environment as independent party. It means that the higher the score of company’s environmental performance, the higher the commitment to pay taxes. This study supports the view that more socially responsible corporations are likely to be less tax aggressive.